Penerapan Strategi Bersaing dengan Pendekatan Five Porter Analysis pada Zonecoffe Temanggung - Sahi, Ahmad; Asye Rachmawaty; Anna Noviana (Program Studi Administrasi Bisnis, 2024)
Coffee consumption has become an attraction and a popular lifestyle within Indonesian society, leading to a growing number of coffee producers and positioning Indonesia as the third-largest coffee producer in the world. This growth has resulted in competition among coffee producers, requiring them to adopt competitive strategies, innovate, and demonstrate creativity to gain consumer acceptance. Zonecoffee Temanggung, which is located on Jl. Raya Parakan, Wonosobo, Kalianggrung, Tlahap, Kledung sub-district, Temanggung district, Central Java, focuses on coffee production and was only established in 2024. An in-depth analysis is therefore needed so that the existence of this coffee producer can continue to grow and develop. Conducting competitive strategy research using the 5 Forter's Force method will be a reference to what the competition for coffee producers will be like in the future and what strategies will be applied in running this business so that it continues to win the hearts of customers. In detail, it will be discussed about the five Forter's Force strategy methods, including the following: analysis of the threat of new entrants to coffee producers, bargaining power of suppliers, bargaining power of buyers, the threat of substitute products, and competition between coffee producers. By conducting this research, a reference to the competitive strategy at Zonecoffee is obtained.